Masticatory and neck muscles` isometric endurance and their relation to upper limb isometric grip strength in sport climbers - preliminary investigation - Baszczowski, M.; Dolina, A.; Zawadka, M.; Ginszt, M.; Czarnecki, A.; Ginszt, A.; Gawda, P. (Medicina, 2025)
Background and Objectives: Sport climbing`s popularity has grown with its inclusion in the Olympics and increased accessibility. Understanding the relationship between hand dominance, grip strength, endurance, and the involvement of masticatory and neck muscles can provide valuable insights into the neuromuscular adaptations specific to sport climbing, potentially aiding performance optimization and injury prevention in intermediate and advanced climbers. This study analyzes if the dominant hand has greater isometric endurance and isometric manual grip strength parameters than the non-dominant one and examines its relation to the masticatory and neck muscles in intermediate and advanced sport climbers.